2022
DOI: 10.3389/fcdhc.2021.807201
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cardiometabolic Syndrome and its Association With Body Shape Index and A Body Roundness Index Among Type 2 Diabetes Mellitus Patients: A Hospital-Based Cross-Sectional Study in a Ghanaian Population

Abstract: Cardiometabolic syndrome (MetS) is closely linked to type 2 diabetes mellitus (T2DM) and is the leading cause of diabetes complications. Anthropometric indices could be used as a cheap approach to identify MetS among T2DM patients. We determined the prevalence of MetS and its association with sociodemographic and anthropometric indices among T2DM patients in a tertiary hospital in the Ashanti region of Ghana. A comparative cross-sectional study was conducted among 241 T2DM outpatients attending the Komfo Anoky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Likewise, Anto at al. [ 44 ] indicated that only BRI was the independent predictor of MetS and compared to traditional indicators it turned out to be the best. Our study found that BRI had a strong positive correlation with WHtR and WC, and also with BMI and fat mass (%).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Anto at al. [ 44 ] indicated that only BRI was the independent predictor of MetS and compared to traditional indicators it turned out to be the best. Our study found that BRI had a strong positive correlation with WHtR and WC, and also with BMI and fat mass (%).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the prevalence of MetS was estimated based on the IDF and/or NCEP-ATP III 2004 criteria. Among the articles, eleven studies reported the prevalence of MetS based on both NCEP-ATP III 2004 and IDF criteria [32,38,53,39,40,[43][44][45]48,49,51], fourteen studies reported based solely on NCEP-ATP III 2004 criteria [25,26,42,46,50,52,[28][29][30][31]33,35,36,41] and five studies reported based on IDF criteria alone [24,27,34,37,47] . Additionally, nine studies reported the prevalence of MetS subcomponents based on NCEP-ATP III 2004 criteria [25,26,31,35,[40][41][42][43][44] and six studies based on IDF criteria [24,27,40,43,44,47].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…It combines waist circumference (WC) and height to describe a person's body shape, and it is more re ective of the proportion of body fat and visceral fat compared to traditional indicators such as BMI, WC, and hip circumference(HC) [7][8][9][10]. As a novel measurement index, BRI has shown good ability in predicting fat distribution (R 2 of predicting male body fat percentage is 0.78; R 2 of predicting male visceral fat percentage is 0.56) [11], and has also been used to predict diabetes, hypertension, metabolic syndrome, and cardiovascular diseases [12][13][14]. Previous studies have indicated a signi cant correlation between BRI and metabolic syndrome and insulin resistance [15], making it a risk factor for diseases such as diabetes, coronary artery disease, and cardiovascular diseases [16][17][18].…”
Section: Introductionmentioning
confidence: 99%